1994
DOI: 10.2307/2500328
|View full text |Cite
|
Sign up to set email alerts
|

Peasant or Proletarian? Militant Pskov Workers in St. Petersburg, 1913

Abstract: Like all working classes everywhere and at all times, the Russian working class on the eve of the revolution was internally differentiated. As Diane Koenker and William Rosenberg have recently emphasized, Russian workers were distinguished from one another by skill level, strength of ties to the land, gender, age and other factors. And those distinctions mattered: they affected the form and intensity of workers’ anti-regime actions which extended from reluctant submission to un-rehearsed rebellion, to organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Elsewhere we have demonstrated that proletarianization variables were significantly correlated with labor militance in St. Petersburg (Brym and Economakis 1994 Kruze 1961, pp. 255, 261;Tomchevich 1972, p. 12).…”
Section: Proletarianization Militance and Marriagementioning
confidence: 88%
“…Elsewhere we have demonstrated that proletarianization variables were significantly correlated with labor militance in St. Petersburg (Brym and Economakis 1994 Kruze 1961, pp. 255, 261;Tomchevich 1972, p. 12).…”
Section: Proletarianization Militance and Marriagementioning
confidence: 88%
“…Elsewhere we have demonstrated that proletarianization variables were significantly correlated with labor militance in St. Petersburg (Brym and Economakis 1994). Worker blacklists (chernye spiski) were compiled by the St. Petersburg Society of Factory and Mill Owners during the strike wave of 1913.…”
Section: Proletarianization Militance and Marriagementioning
confidence: 94%
“…In contrast, many Western analysts hold that the strikers were &dquo;gray&dquo; workers with strong ties to the land and to their villages: semi-urbanized peasants rebelling against life under an alien and hostile industrial regime (Brym and Economakis 1994). From their point of view, the strikes expressed the demands of a flourishing working-class community.…”
mentioning
confidence: 99%